Effects of selected treatments and techniques for the reclamation and improvement of cheringa acid sulfate soil under rice production in the coastal plain of Coxs Bazar - Khan, Md Harunor Rashid; Kabir, Syed Monzur; Bhuiyan, Md Mukaddas Ali (Journal of the Asiatic Society of Bangladesh, Science, 2016)
Modified-Plain-Ridge-Ditch techniques (Tech 1: pyrite layer at top, jarosite layer at middle and top soil at the bottom of ridge; Tech 2: top soil at top, pyrite at middle and jarosite layer at the bottom of ridge) were used under field condition for the reclamation and improvement of the pre-leached Cheringa acid sulfate soil manipulated by basic slag (BS20 and BS30: basic slag 20 and 30 t ha-1) and aggregate size (A20 and A30: aggregate sizes of soil less than 20 and 20-30 mm) treatments. The initial soil had very low pH (3.4), high ECe (1.6 S m-1) and pyrite content (76 g kg-1). Magnesium content (water soluble + exchangeable = 5.38 c mol kg-1) of the soil was about 3 fold than that of Ca (1.71 c mol kg-1), and Al content (9.22 c mol kg-1) was highly toxic level. The pre- and post harvested soil data revealed that the properties of the soil was strongly (p?0.05) influenced by the different treatments. The average soil data of all the treatments at post harvesting of rice cultivars were increased by 1.5 units for soil pH(dry) and 12 to 463% for the contents of N, P, Ca and Mg, while decreased the concentrations of Fe, Al, Na, Cl- and SO4 2- by 27 to 93% compared with the initial soil. The maximum growth and yield of rice grain (5.4 t ha-1) were attained by the local cultivar Pizam compared with the high yielding variety BR 14 (5.1 t ha-1) by the A20BS30 treatment in the ridges of the Tech 2. The lowest grain yields of 0.03 (BR 14) and 0.07 (Pizam) t ha-1 were recorded for the control plots (where no amendment was applied). The other treatments also resulted in a significant (p?0.05) improved performance on plant production compared with the control. J. Asiat. Soc. Bangladesh, Sci. 42(1): 29-40, June 2016